2022
DOI: 10.3390/fishes7020065
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Intestinal Characteristics of Largemouth Bass (Micropterus salmoides) and Intestinal Flora with Different Growth Rates

Abstract: To explore the causes of different growth rates among juvenile populations of largemouth bass, in the present study, a batch of largemouth bass juveniles reared under the same conditions were divided into a fast-growing group and a slow-growing group. We used histological, enzymatic and molecular biology methods to analyze and determine their histomorphological changes, digestive enzyme activity and intestinal floral composition. The fast-growing group had a significantly (p ≤ 0.01) greater intestinal fold hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The intestinal FH and MT are the well-defined parameters for the health status in the intestine of fish [27]. The absorption of nutrients in the intestine is determined by the villi length of the intestinal fold [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal FH and MT are the well-defined parameters for the health status in the intestine of fish [27]. The absorption of nutrients in the intestine is determined by the villi length of the intestinal fold [28].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of medical plant-derived extracts on intestinal microbiota are increasingly reported in aquaculture [5,31,32]. The indexes of OTUs, Chao 1, and Shannon are usually used to evaluate the species abundance and richness of the intestine microbiota [27,33]. A high microbiota diversity is generally considered beneficial for intestinal health [34].…”
Section: Discussionmentioning
confidence: 99%
“…The study of intestinal histology can help to investigate the effect of diets on intestinal morphology and health of farmed fish. The intestine, pivotal in nutrient metabolism and absorption, and its histology, particularly villi dimensions, offer insights into absorption efficacy, contributing to growth (Guan et al, 2021; Su et al, 2022). In this study, the intestinal histology analysis revealed that chitosan supplementation in A. stellatus 's diet led to a notable increase in both the height and width of intestinal villi.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbes play a key role in nutrient digestion, absorption and maintenance of the homeostasis of the host metabolism and immune systems [ 48 ]. Generally, the indexes of OTUs, Chao1 and Simpson obtained by alpha diversity analysis are used to reflect the species diversity and abundance of intestinal microbiota [ 49 , 50 ]. It was verified that the diversity or abundance of the intestinal microbiota of juvenile American eels was significantly affected by the dietary histamine levels at 350 mg/kg or 534 mg/kg [ 13 ].…”
Section: Discussionmentioning
confidence: 99%